Efektivitas Empty Chair Technique Untuk Meningkatkan Kepercayaan Diri Siswa Dalam Memilih Karir - Diva Alfira Junaidi (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2026)
This study was motivated by the low level of students' self-confidence in choosing careers, which was characterized by doubt, anxiety, and uncertainty regarding their abilities to make career decisions. The purpose of this study was to determine the effectiveness of the Empty Chair Technique in improving students' self-confidence in choosing careers at SMA Negeri 12 Enrekang. This study employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The population consisted of all tenth-grade students at SMA Negeri 12 Enrekang, while the sample comprised 10 students selected through purposive sampling. Data were collected using a self-confidence questionnaire in career selection and analyzed using descriptive and inferential statistics, including the normality test and paired sample t-test with the assistance of SPSS version 26. The results showed that students' self-confidence in choosing careers increased after participating in group counseling sessions utilizing the Empty Chair Technique. The mean pretest score was 106.10, which increased to 121.70 in the posttest.